Factors affecting career advancement of female chefs / Siti Ida Isnainie Md Mubin, Mohamad Abdullah Hemdia and Srinita Isjkarim - Md Mubin, Siti Ida Isnainie; Hemdi, Mohamad Abdullah; Isjkarim, Srinita (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
Female chefs experience many challenges in the male-dominated chef profession. Research shows that female chefs face challenges of promotion, low pay, work-life balance, burnout and sexual harassment. The current study intends to unveil factors affecting career advancement of female chefs. Specifically, whether factors such as equality of opportunities, work-family conflict, gender discrimination, and career commitment have significant influence on career advancement of female chefs. Survey data were gathered from female chefs at the level of non-supervisory and operational employees attached to 4 and 5-star rated hotels located in the state of Selangor and Kuala Lumpur Malaysia. 248 usable questionnaires were returned and analyzed. The results showed that equality of opportunities and work-family conflict significantly influenced career commitment and career advancement. While, career commitment partially mediated the relationship between equality of opportunities and career advancement. Identification of factors affecting career advancement of female chefs help hotel managers to effectively develop initiatives to attract and retain female chefs in the profession and enabling their opportunities and career prospects in the hospitality industry.